Tradition and Transformation in Christian Art - Tsakiridou, C.A., author.
1 online resource (242 pages)
Keywords: Tradition and Transformation in Christian Art approaches tradition and transculturality in religious art from an Orthodox perspective that defines tradition as a dynamic field of exchanges and synergies between iconographic types and their variants. Relying on a new ontology of iconographic types, it explores one of the most significant ascetical and eschatological Christian images, the King of Glory (Man of Sorrows) This icon of the dead-living Christ originated in Byzantium, migrated west, and was promoted in the New World by Franciscan and Dominican missions. Themes include tensions between Byzantine and Latin spiritualities of penance and salvation, the participation of the body and gender in deification, and the theological plasticity of the Christian imaginary. Primitivist tendencies in Christian eschatology and modernism place avant-garde interest in New Mexican santos and Greek icons in tradition.